The Legal Status of Nikka Sibateng in Accordance with Islamic Law: A Study on the Bugis Bone Community - Jasmin, Suriah Pebriyani; Sahrani, Dea (Constitutional Law Review, 2024)
This research explores the legal position of nikka sibateng (spiritual marriage) within the Bugis Bone community, particularly in Gareccing Village, Tonra District, Bone Regency. Nikka sibateng involves a secretive union conducted without witnesses, typically following a lawful Islamic marriage, and excludes religious institutions like the Office of Religious Affairs. Participants justify this practice as a means to solidify their bond, believing it ensures their union despite opposition from some community members. Critics argue that nikka sibateng can have negative repercussions, especially for children if one partner dies, as they believe the surviving spouse will soon follow. This view is rooted in local customs and culture. The research aims to understand the practice of nikka sibateng and its standing in Islamic law. Employing a qualitative descriptive approach, the study uses normative juridical, normative empirical, anthropological, and sociological perspectives. Findings reveal that nikka sibateng was once a tradition in Gareccing Village but is no longer practiced. Importantly, the study concludes that nikka sibateng, as a tradition in this community, does not contradict Islamic law or Indonesia's prevailing marriage laws